2019
DOI: 10.1016/j.nicl.2019.101977
|View full text |Cite
|
Sign up to set email alerts
|

Altered motor dynamics in type 1 diabetes modulate behavioral performance

Abstract: Type 1 diabetes (T1D) has been linked to alterations in both brain structure and function. However, the neural basis of the most commonly reported neuropsychological deficit in T1D, psychomotor speed, remains severely understudied. To begin to address this, the current study focuses on the neural dynamics underlying motor control using magnetoencephalographic (MEG) imaging. Briefly, 40 young adults with T1D who were clear of common comorbidities (e.g., vascular disease, retinopathy, etc.) and a demographically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
2
5
0
Order By: Relevance
“…Our behavioral results confirm that despite adequate clinical development of T1D, several cognitive processes are progressively affected by this disease, as revealed by the tendency toward a deterioration in the behavioral performance of T1D patients (e.g., Embury et al, 2019;Gallardo-Moreno et al, 2015;González-Garrido et al, 2019). Brands et al (2005) reported that cognitive dysfunction in T1D patients is characterized by a slowing of mental speed.…”
Section: Discussionsupporting
confidence: 82%
“…Our behavioral results confirm that despite adequate clinical development of T1D, several cognitive processes are progressively affected by this disease, as revealed by the tendency toward a deterioration in the behavioral performance of T1D patients (e.g., Embury et al, 2019;Gallardo-Moreno et al, 2015;González-Garrido et al, 2019). Brands et al (2005) reported that cognitive dysfunction in T1D patients is characterized by a slowing of mental speed.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, increased gamma activity in HAND during reorienting may reflect a compensatory mechanism with increasing age, such that those with HAND recruit brain reserve networks in VAN cortices to a comparatively greater extent during high attentional demands. A large body of literature focuses on compensatory processes in older adults [ 68 , 120 , 121 ], as well as in pathological conditions like diabetes [ 122 , 123 ] and HIV [ 37 , 76 ], and/or a similar framework may be at play here. Our behavioral findings would certainly support such a conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…For the direct effect, patients with higher spontaneous beta power tend to have poorer psychomotor performance. For the indirect effect, patients with higher spontaneous beta power tend to have greater MRBD ( Heinrichs-Graham et al, 2018 , Heinrichs-Graham and Wilson, 2016 , Trevarrow et al, 2019 , Wilson et al, 2014 ), and greater MRBD predicts better psychomotor performance ( Babiloni et al, 2000 , Embury et al, 2019 , Heinrichs-Graham et al, 2020 , Trevarrow et al, 2022b , Van Hoornweder et al, 2022a , Van Hoornweder et al, 2022b ). The indirect effect partially offsets the negative effects of the direct effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that response time was related to MRBD in healthy people, while the correlation was impaired in MDD ( Jiang et al, 2019 ). Notably, studies from other groups have found that more pronounced MRBD predicted better task performance in individuals with ( Embury et al, 2019 , Trevarrow et al, 2022b ) or without pathological conditions ( Babiloni et al, 2000 , Heinrichs-Graham et al, 2020 , Van Hoornweder et al, 2022a , Van Hoornweder et al, 2022b ). However, some researchers observed no significant relationship between behavioural performance and MRBD ( Heinrichs-Graham et al, 2018 , Hübner et al, 2018 , Rossiter et al, 2014 , Schmiedt-Fehr et al, 2016 , Spooner et al, 2022 , Spooner et al, 2021 , Vallesi et al, 2010 ), while others claimed that higher MRBD was associated with worse performance ( Heinrichs-Graham and Wilson, 2016 , Johari and Behroozmand, 2020 , Kurz et al, 2020 , Xifra-Porxas et al, 2019 ).…”
Section: Introductionmentioning
confidence: 94%